1988
DOI: 10.1016/0014-5793(88)80344-2
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetry of rapid chloride responses to inositol trisphosphate and calcium in Xenopus oocytes

Abstract: Shallow injection of inositol 1,4,%trisphosphate (IP,) near the animal pole of the Xenopus oocyte resulted in a large depolarizing current that decayed rapidly. A similar injection near the vegetal pole produced a much smaller response characterized by a significantly slower rate of decay. Injection of CaCI, near the animal pole of the oocyte resulted in a large depolarizing current characterized by rapid rise and decay times. Injection near the vegetal pole of the cell produced responses that exhibited simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 11 publications
3
20
2
Order By: Relevance
“…In parallel with the Ca2+ imaging, we voltage-clamped the oocytes; the results obtained were consistent with the imaging data in that all the above agonists evoked responses that are believed to depend on inositol trisphosphate-mediated release of intracellular Ca2 , which in turn activates chloride channels (2,(4)(5)(6). The number of agonist-responsive oocytes detected electrophysiologically was similar to that found by imaging.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In parallel with the Ca2+ imaging, we voltage-clamped the oocytes; the results obtained were consistent with the imaging data in that all the above agonists evoked responses that are believed to depend on inositol trisphosphate-mediated release of intracellular Ca2 , which in turn activates chloride channels (2,(4)(5)(6). The number of agonist-responsive oocytes detected electrophysiologically was similar to that found by imaging.…”
supporting
confidence: 71%
“…When the translated mRNA produces a receptor or ion channel, it is usually biochemically functional, exhibiting the appropriate pharmacological and electrophysiological properties. A number of recent studies have dealt with de novo expression of neurotransmitter receptors, as detected by electrophysiological and biochemical methods (2)(3)(4)(5), making the oocyte an excellent system to detect newly expressed ion channels or ion channel-linked receptors in cloning strategies.…”
mentioning
confidence: 99%
“…Ca 2+ -activated C1-channels are also thought to be clustered into the animal pole [26] and perhaps even clustered in regions of different densities within this pole [27]. Several findings support the idea that C1-channels are clustered.…”
Section: Inactivation Of Ca 2+ Influxmentioning
confidence: 79%
“…Nonrandom distribution of any of the components involved in signal transmission, distal to the receptor, would conceivably result in a locally different response upon application of agonist. It has indeed been shown that injection of IP3 at the animal pole elicits much larger currents than at the vegetal pole [19,135], whereas conflicting reports have been published on an asymmetry of the response to injection of calcium [135,150]. Dreyfus et al [44] studied the distribution of a membrane-associated butyrylcholinesterase after injection with cDNA-derived mRNA.…”
Section: Translation Assembly Modification and Sortingmentioning
confidence: 97%